(untitled) (Al-Academy, 2023)
By reading the book (Endless Forms Most Beautiful: The New Science of Evo Devo) by Sean B. Carroll, new horizons opened up about the nature of the formation of the living organism. Although he presented the idea that the artist was influenced by the material assets of nature in his holographic art formations, the new science of Evo-Devo (Evolutionary Developmental Science) provided models worth standing on when comparing the similarity of the formation of living organisms on the one hand, and the formation of works of art with holographic organic bodies on the other. But the excitement lies in the fact that the formation of living natural organisms is often driven by subtle intelligent mechanisms that are different from the mechanisms used by the artist in stereoscopic organic formations. Holographic art formation is carried out with preconceived schemes and perceptions stuck in the artist’s mind, which is not necessarily similar to the tools of nature in shaping the body of a living organism. This study comes to address (the stages of production for the artist) more than it addresses (the final product) of the holographic artwork, in an attempt to imagine the extent to which the artist was involuntarily or involuntarily influenced by nature as recounted by Sean Carroll in writing, relying on scientific experiments in evo devo science. Based on the exceptional content in the book (Endless Forms Most Beautiful: The New Science of Evo Devo), this study comes to complement one of the building blocks of our perception of the artist’s plastic abilities and the relationship of his holographic visual perceptions with nature, and explores the idea of formation and its growth beyond the final form of holographic artworks.